Analisis Kualitas Pelayanan di Kantor Desa Bola Kecamatan Bola Kabupaten Wajo Berdasarkan Dimensi SERVQUAL untuk Kepuasan Masyarakat - Muhammad Akram; Burhanuddin Burhanuddin; Erna Erna; Gustina Gustina (Politeknik Kampar, 2025)
This study aims to describe the quality of services at the Bola Village Office, Bola District, Wajo Regency. The type of research used is descriptive qualitative research, with data collection techniques through observation, interviews, and documentation. Data analysis was carried out through several stages: data reduction, data presentation, and conclusion drawing. To test the validity of the data, this study applied credibility, transferability, dependability, and confirmability tests to ensure the results could be accountable and applicable in broader contexts. The analysis results, based on the five SERVQUAL dimensions, indicate that the service quality at the Bola Village Office is considered good. The first dimension, reliability, shows that the services provided are in line with the existing standard operating procedures (SOPs), supported by adequate training for the staff. This ensures that the services provided are timely and consistent with the public's expectations. The second dimension, responsiveness, shows that the staff can provide quick responses through the implemented priority system, allowing issues faced by the public to be handled promptly. The third dimension, assurance, is demonstrated by the professionalism of the staff and the security of the data. This provides a sense of security to the public, knowing that their data is managed properly and securely. The fourth dimension, empathy, is demonstrated by the personal attention given by the staff to the community. The staff not only provides efficient services but also cares about individual needs, fostering a more humanistic and close relationship with the residents. Meanwhile, the fifth dimension, physical facilities, is adequate to support smooth service delivery, though some improvements are still needed in terms of cleanliness and maintenance. Overall, the findings of this study emphasize the importance of quality-based service in improving public satisfaction. With services that prioritize reliability, responsiveness, assurance, empathy, and adequate facilities, the Bola Village Office can enhance service quality and provide greater satisfaction to the community.